Demokrasi pancasila sebagai dasar sistem politik indonesia - Ahmad, Raffi (Maliki Interdisciplinary Journal, 2026)
Pancasila Democracy is the main foundation and distinctive identity of the political system in Indonesia. In contrast to liberal or socialist democratic concepts, Pancasila Democracy integrates the values of divinity, humanity, unity, deliberation, and social justice into every aspect of state life. This study aims to analyze in depth the conceptual interpretation of Pancasila Democracy, its development genealogy in the trajectory of Indonesian political history, and its implementation and challenges in the modern era. The research method used is a literature review (library research) with a descriptive-analytical approach using authoritative scientific sources. The analysis indicates that Pancasila Democracy places the principle of deliberation for consensus above absolute voting to maintain national stability and unity. However, in the modern era of information openness, this political system faces significant challenges such as social polarization, identity politics, and the threat of oligarchy. Therefore, strengthening transparent political institutionalization and revitalizing Pancasila values in the younger generation are absolute prerequisites to maintain the continuity of a healthy and equitable democratic system in Indonesia.